2015
DOI: 10.1039/c5sc01867f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of monohaptoallylpalladium species: internal coordination as a driving force in allylic alkylation chemistry

Abstract: Structural and reactivity studies of internally coordinated monohaptoallylpalladium(ii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…Intrigued by the mechanistic complexity of this system, we have sought structural characterization of intermediates . One such venture is depicted in Scheme , where equimolar amounts of chlorocarboxylic acid cis - 41 , a Pd(0) source and chiral ligand L3a were admixed.…”
Section: Enantioselective Synthesis Of Cyclobutenesmentioning
confidence: 99%
“…Intrigued by the mechanistic complexity of this system, we have sought structural characterization of intermediates . One such venture is depicted in Scheme , where equimolar amounts of chlorocarboxylic acid cis - 41 , a Pd(0) source and chiral ligand L3a were admixed.…”
Section: Enantioselective Synthesis Of Cyclobutenesmentioning
confidence: 99%
“…Apart from the obvious requirements on solubility, the small molecule may also not tolerate the presence of the alignment medium (or vice versa) and decompose (or lead to destabilization or decomposition of the medium). However, after rigorous trials, compatible media were found for moderately unstable compounds like Pd complexes involved in homogeneous catalysis [57,58] and even very reactive organolithium species. [59][60][61] For LLCs, sample preparation generally involves preparation of the alignment medium first, i.e.…”
Section: Alignment Mediamentioning
confidence: 99%
“…In this regard, the Maulide group pioneered the investigations of the reactivity of strained cyclic π-allylpalladium complexes by using 2-oxabicyclo[2.2.0]­hex-5-en-3-one and 4-chlorocyclobut-2-ene carboxylic acid as substrates, achieving the diastereoselective and enantioselective synthesis of functionalized cyclobutenes (Scheme b) . In 2013, the same group further studied the structure and reactivity of cyclobuten-3-yl palladium complexes in detail and discovered that the strained cyclic π-allylpalladium intermediates were inclined to undergo electrocyclic ring opening to deliver dienyl palladium species . Despite the remarkable progress, the laborious access and instability of the allylic precursors restrict the comprehensive investigation of strained cyclic π-allylpalladium complexes.…”
mentioning
confidence: 99%